Diagnosis Klinis dan Tatalaksana Rawat Jalan pada Abses Peritonsil Sinistra: Sebuah Laporan Kasus - Vania Widyadhari Damayanti; Mukhlis Imanto (CV. Jasa Sukses Abadi, 2026)
Peritonsillar abscess is the most common complication of acute tonsillitis and is characterized by the accumulation of pus within the peritonsillar space. If left untreated, it may lead to serious complications, making early recognition and appropriate management essential. In patients with characteristic clinical findings, the diagnosis can often be established based on history taking and physical examination without additional investigations. This case report describes the clinical diagnosis and outpatient management of a left-sided peritonsillar abscess in a 46-year-old man presenting with a two-week history of left neck swelling, progressive sore throat, odynophagia, dysphagia, trismus, hot potato voice, hypersalivation, and fever. Oropharyngeal examination revealed an erythematous and bulging left peritonsillar swelling, causing medial displacement of the left tonsil and rightward deviation of the uvula. A clinical diagnosis of left peritonsillar abscess was established. Although hospitalization was recommended, the patient declined admission and was managed as an outpatient with oral cefixime, metronidazole, methylprednisolone, and paracetamol. Comprehensive education was provided regarding adequate rest, hydration, oral hygiene, smoking cessation, medication adherence, and recognition of warning signs requiring immediate medical attention. Outpatient treatment was considered appropriate because the patient had no evidence of airway compromise, dehydration, sepsis, significant comorbidities, or inability to tolerate oral medication. This case highlights that peritonsillar abscess can be accurately diagnosed clinically and that carefully selected patients may be safely managed on an outpatient basis with appropriate follow-up and patient education to minimize the risk of complications.